Teaching Computer System-DMT DESIGN(SA).1 - A. O. Shteynberg; O. V. Davletov (Образование и наука)
Тhe paper introduces the training computer system of sub- agential type based on a didactic multidimensional technology. The methodology bases incorporate the systematic activity approach, some elements of artificial intelligence theory, and the instrumental didactic theory and technology developed by Scientific Experimental Laboratory at Bashkirsky State Pedagogical University. The above training system – Didactic Multidimensional Technology Design of Sub-Agential Type (DMT_DESIGN (SA).1) – has been developed for raising teachers’ technological competence and creativity regarding both the general and vocational education. Its training structure is specified by invariant socio-cultural and anthropological bases; logically semantic modeling of course materials is provided. The research data can be used by people, engaged in developing educational information technologies; practicing teachers; and post-graduates conducting research and implementing the findings.